«Cancel culture» and cyber-aggression: issues of legal assessment - Yaremko, Oksana (Actual problems of law (Aktual’ni problemi pravoznavstva), 2021)
The article focuses on current safe and tolerant communication issues in the global information network «Internet». It is noted that society and Internet users are ambivalent about the phenomenon of «cancel culture». The content of this phenomenon and its terminological features are investigated. It is proposed to interpret «cancel culture» as a way to bring people or groups (famous or empowered) to justice for legal, social, ethical violations by refusing to support and (or) by public condemnation, mainly on social networks (unfollowing accounts, boycott of its projects). The essence of «cancel culture» is revealed through the prism of legal values (tolerance, justice, freedom of speech, humanity, etc.). Problematic aspects of distinguishing «culture» from forms of cyber aggression (trolling, hatred, cyberbullying, harassment, catcalling, shaming, blaming, flaming, hosting, outing, queerbaiting) are analyzed. It is noted that, unlike these forms of destructive communication on the Internet, «cell culture» is essentially a form of communication aimed at combating aggression, the struggle for justice, and, consequently, is a positive socio-cultural phenomenon. Attention is drawn to the problematic aspects of legal liability for destructive communication on social networks, including abuse during «cancelling».